Pengaruh Strategi Manajemen Sumber Daya Manusia (Msdm), Kepemimpinan Pelayanan, Dan Disiplin Kerja Terhadap Kepuasan Kerja (Studi Pada PT Cilegon Fabricators) - FAJRIN, ANDINI; Prahiawan, Wawan (Jurnal Manajemen dan Bisnis, 2024)
This study aims to determine the effect of Human Resource Management Strategy, Servant Leadership, and Work Discipline on Job Satisfaction. In determining the number of samples using the Slovin formula and the results obtained were 92 respondents and for sampling using purposive sampling. For data analysis, a model test was used using the SmartPLS (Partial Least Square) analysis tool version 3.0. From the results of the SmartPLS 3.0 calculation, the research results with a t-statistic value greater than t-table, namely 1.96, the conclusions are: (1) showing that Human Resource Management Strategy has an effect on job satisfaction, (2) servant leadership has a positive effect on job satisfaction, (3) work discipline has a positive effect on job satisfaction.